Elites, paradigm and change in transnational perspective - Thakur, Rudranand, 1939; Gaur, M. K.; Indian Institute of Public Administration (New Delhi : Indian Institute of Public Administration, 1988)
Contributed articles.
Includes indexes.
Bibliography: p. 251-265.
Keywords: Elite (Social sciences)